Association between positive history of essential tremor and disease progression in patients with Parkinson's disease - Ruwei Ou (Nature Portfolio, 2020)
Abstract This study aimed to explore the effect of pre-existing essential tremor (ET) history on the disease progression of Parkinson’s disease (PD). We recruited and followed-up a group of PD patients from March 2009 to July 2020. The ET history of each patient was obtained by retrospective interviews or past medical records. Cox proportional hazards models with inverse probability of treatment weighting (IPTW) were used to estimate the hazard ratio (HR) with 95% confidence intervals (CIs). Of 785 patients who completed the followed-up visits, 61 patients (7.8%) reported a history of pre-existing ET. Cox regression models after IPTW indicated that the positive ET history in patients with PD was protective against time to United PD Rating Scale III 14-point increase (HR = 0.301, 95% CI = 0.134–0.678, P = 0.004), time to akinesia and rigidity 8-point increase (HR = 0.417, 95% CI = 0.218–0.796, P = 0.008), time to conversion to Hoehn and Yahr stage 3 (HR = 0.356, 95% CI = 0.131–0.969, P = 0.043), time to develop dyskinesia (HR = 0.160, 95% CI = 0.037–0.698, P = 0.015), and time to Montreal Cognitive Assessment 3-point decrease (HR = 0.389, 95% CI = 0.160–0.946, P = 0.037), but had no relationship with time to tremor 4-point increase (HR = 1.638, 95% CI = 0.822–3.266, P = 0.161) and time to death (HR = 0.713, 95% CI = 0.219–2.319, P = 0.574). Our study indicated that ET history in patients with PD is associated with a benign prognosis with slower motor and non-motor progression.